Un modello operativo per la didattica delle lingue online: l’Unità Didattica Digitale - La Grassa, Matteo (Educazione Linguistica Language Education, 2021)
Referring to teaching Italian language online, the general tendency has been to use the same patterns for both face-to-face and e-learning courses. Moreover, teaching Italian online has been considered mainly as scaffolding for teaching Italian in classroom (e.g. in several blended courses). Although many e-learning activities can also be successfully exploited in face-to-face lessons, currently a process of ‘separation’ between the two different teaching/learning contexts is ongoing: these two educational channels have today different status and are bounded by a ‘non-competitive’ correlation. In this framework the need arises to elaborate new operational models suitable for e-learning. This article will present the main characteristics of a model, specifically elaborated to be used in technological learning environment, that we called Digital Didactic Unit.